2011
DOI: 10.1097/ncc.0b013e31820d4f05
|View full text |Cite
|
Sign up to set email alerts
|

Daily-Life Physical Activity and Related Factors Among Patients With Cancer Receiving Chemotherapy in Taiwan

Abstract: Strategies to enhance cancer patients' physical activity level should include counseling patients to remain employed, offering symptom management such as pain relief, advising energy reserve skills, and providing appropriate places for exercise or walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Second, exhaustion was indicated by a self response of “more than 3 days a week” to either of the following statements: “I felt everything I did was an effort” or “I could not get going” on the Center for Epidemiological Studies‐Depression Scale . Third, physical inactivity was measured by the Taiwan International Physical Activity Questionnaire‐Short Form . The criterion of the minimum weekly energy expenditure was 383 Kcal for men and 270 Kcal for women .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, exhaustion was indicated by a self response of “more than 3 days a week” to either of the following statements: “I felt everything I did was an effort” or “I could not get going” on the Center for Epidemiological Studies‐Depression Scale . Third, physical inactivity was measured by the Taiwan International Physical Activity Questionnaire‐Short Form . The criterion of the minimum weekly energy expenditure was 383 Kcal for men and 270 Kcal for women .…”
Section: Methodsmentioning
confidence: 99%
“…6,19 Third, physical inactivity was measured by the Taiwan International Physical Activity Questionnaire-Short Form. 20 The criterion of the minimum weekly energy expenditure was 383 Kcal for men and 270 Kcal for women. 6 Fourth, slow walking speed was indicated by a usual walking speed slower than the sex-and height-adjusted criterion-specific thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise during cancer treatment has been shown to have a beneficial effect on pain for breast cancer patients [44][45][46][47]. In a similar study to ours, Liou et al [45] surveyed the daily physical activity levels of individuals who were undergoing chemotherapy, but were not diagnosed with CIPN. These authors reported that those patients who received the recommended 150 min/wk of moderate activity reported significantly less symptoms of pain than their sedentary counterparts.…”
Section: Discussionmentioning
confidence: 79%
“…On the contrary, the increased recognition on the necessity of health care due to diagnosis with cancer leads to physical activities. The amount of their physical activity is higher than that of normal middle-aged adults ( Liou et al, 2011 ) and the evidence for the effect of physical activity on the prevention of cancer is rapidly increasing, suggesting that the physical activity of cancer patients is attracting attention as a non-pharmacological intervention during hospitalization ( Luctkar-Flude et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%